2014
DOI: 10.1523/jneurosci.0903-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Synaptic Vesicle-Pool Depletion and Replenishment Can Account for the Interspike Interval Distributions and Nonrenewal Properties of Spontaneous Spike Trains of Auditory-Nerve Fibers

Abstract: In mammalian auditory systems, the spiking characteristics of each primary afferent (type I auditory-nerve fiber; ANF) are mainly determined by a single ribbon synapse in a single receptor cell (inner hair cell; IHC). ANF spike trains therefore provide a window into the operation of these synapses and cells. It was demonstrated previously (Heil et al., 2007) that the distribution of interspike intervals (ISIs) of cat ANFs during spontaneous activity can be modeled as resulting from refractoriness operating on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 66 publications
3
78
0
Order By: Relevance
“…In a recent study (Peterson et al 2014), negative ISI correlations observed in auditory nerve fibres have been attributed to synaptic depression of the ribbon synapse that generates the input to a nerve fibre. In that case, the spike train was modeled as a thinned-out version of stochastic transmitter release events of the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (Peterson et al 2014), negative ISI correlations observed in auditory nerve fibres have been attributed to synaptic depression of the ribbon synapse that generates the input to a nerve fibre. In that case, the spike train was modeled as a thinned-out version of stochastic transmitter release events of the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cat data were kindly provided by Philip X. Joris and are the same as those used in Figure 6 of Joris and Yin (). The remaining cat data were recorded by Peter Heil and Dexter R. F. Irvine and are used in Heil and Irvine (), Heil and Neubauer (), Heil et al (), and Peterson et al (). The gerbil data were kindly provided by Jérôme Bourien and are the same as those used in Figure 5 of Bourien et al ()…”
Section: Spontaneous Activity In Anfs Of Mammalsmentioning
confidence: 99%
“…Note that, for intermediate T , shuffling leads to an increase in F ( T ). Panels D–E modified from Peterson et al ()…”
Section: Spontaneous Activity In Anfs Of Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This precision is required in order to, for example, encode ITD in the microsecond range for locating a sound source . The sound pressure level is transduced into the graded receptor potentials of IHCs that then drive firing of postsynaptic SGNs at a rate reflecting the stimulus intensity (rate code) Glowatzki et al, 2008;Peterson et al, 2014). One anatomical feature of IHCs strikingly contrasts the arrangement of calyceal synapses with hundreds of active zones originating from one terminal converging onto a principal cell (Figs.…”
Section: Different Synapse Types Mediate Sound Encodingmentioning
confidence: 99%